Influence of Frontliner Service Quality and Quality Products Towards Customer Loyalty at KSPP Syariah BMT NU East Java Sumbersari Branch - Jannah, Miftakhul; Muhri, M; Pamuji, Alif Endy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This research aims to evaluate the influence of service quality and product quality on customer loyalty at BMT NU Sumbersari. This Sharia Financial Institution is known for its friendly and responsive service as well as savings pick-up and delivery services and sharia financial financing. This research uses a descriptive quantitative approach. The population in this study was 1527. The research sample was determined randomly (random sampling) with the total sample calculated using the Slovin formula numbering 94 people. Data was collected through questionnaires, and analyzed using multiple linear regression. The results of the research obtained using the t test and F test show that the quality of frontliner service partially influences customer loyalty at BMT NU Sumbersari. Product quality partially has no effect on customer loyalty at BMT NU Sumbersari. Frontliner service quality and product quality simultaneously influence customer loyalty at BMT NU Sumbersari. The resulting R2 value of 0.115 (11.5%) can be interpreted to mean that the capability of the frontliner service quality model (X1), product quality (X2) on customer loyalty (Y) is 11.5 percent, and the rest is influenced by other factors.